Anchor & flares : a memoir of motherhood, hope, and service - Braestrup, Kate (Little, Brown, and Company, 2015)
A devoted Unitarian-Universalist family woman recounts the wrenching loss of her first husband and her joyful years of raising a blended family before confronting fears surrounding her son's decision to enlist in the military.